Role of Video laryngoscopy in the Management of Difficult Airway in Modern Anaesthesiology: A Survey - Hussain, Sadam; Nadeem, Syed Muhammad; Bughio, Shehrum; Tanwani, Hanesh; Ahmed, Yaseen; Ali, Fahad; Kanwal, Nazish (Biological and Clinical Sciences Research Journal, 2025)
In patients with anticipated difficult airway, video laryngoscopy (VL) has shown improved laryngeal view, higher success rates, and higher first-attempt success, leading to fewer intubation maneuvers in VL. Objective: To determine the availability, usage factors, restrictions, and preferences of video laryngoscopes in difficult airway management among anesthesiologists in Sindh. Methods: A total of 94 participants were included. A questionnaire was used, which was divided into two parts. The first part contained questions regarding demographic data and difficult airway management. The second part addressed the availability, use, and perception of anesthesiologists toward its use. The data were compiled and analyzed using SPSS version 25. The Shapiro-Wilk test was used to check normality. If the data were non-normal, the median (IQR) was reported. Stratification was performed and post-stratification chi-square or Fisher's exact tests were applied, with a P-value <0.05 considered significant. Results: The mean age of the anesthesiologists was 32.46±5.88 years. The majority (83%, n=78) of participants reported having access to video laryngoscopy. A total of 3 (3.2%) anesthesiologists faced restrictions. The high expense was the reason for not using VLs. First-generation LMA (48.9%), video laryngoscopy (64.9%), and fibreoptic bronchoscopy (42.6%) were the most preferred first, second, and third options for managing the anticipated difficult airways. Conclusion: Most respondents had access to VLs. A very low percentage of participants faced restrictions in using VLs. The high cost of the device is the primary barrier to its use.